2017
DOI: 10.1007/s11274-017-2370-y
|View full text |Cite
|
Sign up to set email alerts
|

The roles of polyamines in microorganisms

Abstract: Polyamines are small polycations that are well conserved in all the living organisms except Archae, Methanobacteriales and Halobacteriales. The most common polyamines are putrescine, spermidine and spermine, which exist in varying concentrations in different organisms. They are involved in a variety of cellular processes such as gene expression, cell growth, survival, stress response and proliferation. Therefore, diverse regulatory pathways are evolved to ensure strict regulation of polyamine concentration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 65 publications
1
43
0
Order By: Relevance
“…One of the major roles of polyamines in the cell is to provide resistance to intracellular and environmental stress, including that caused by ROS, temperature changes, osmotic pressure or other toxic compounds. 1 The activity of T-SOD in the cells of the control decreased by 87.23%, from the initial 0.47 U mL À1 to 0.06 U mL À1 (Fig. 5).…”
Section: Intracellular Antioxidant Enzyme Activity In Chlorellamentioning
confidence: 90%
“…One of the major roles of polyamines in the cell is to provide resistance to intracellular and environmental stress, including that caused by ROS, temperature changes, osmotic pressure or other toxic compounds. 1 The activity of T-SOD in the cells of the control decreased by 87.23%, from the initial 0.47 U mL À1 to 0.06 U mL À1 (Fig. 5).…”
Section: Intracellular Antioxidant Enzyme Activity In Chlorellamentioning
confidence: 90%
“…Polyamines are involved in a variety of cellular processes such as gene expression, cell growth, survival, stress response, and proliferation. Reverse genetic studies in microorganisms showed that deletion of the genes in polyamine metabolic pathways or depletion of polyamines have negative effects on cell survival and proliferation (Gevrekci, 2017). The metabolic use of spermine and spermidine was done in a lesser extent once Enterobacteriaceae , molds, yeasts, and CNS counts were reduced by HPP application.…”
Section: Resultsmentioning
confidence: 99%
“…Putrescine, spermidine and spermine are the most common polyamines in bacteria and fungi. Except for two archaea, polyamines are identi ed in each organism [28,29]. The universal existence proves its importance in organism.…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines are involved in many cellular processes, such as gene expression, cell proliferation, survival and stress response. The reverse-genetic study of microorganisms showed that the gene deletion or polyamine consumption in polyamine metabolism pathway had a negative effect on cell survival and proliferation [29]. In a study on the mutant T.marneffei strain of S-adenosylmethionine decarboxylase (SAMDC), which was the key enzyme of polyamine synthesis, it was found that the mutant strain had poor growth and sporulation capacity on the basic culture medium.…”
Section: Discussionmentioning
confidence: 99%